Uma proposta de uso de materiais lúdicos e espaços da escola para o ensino de geometria - Oliveira, Francisco Roberto de (2018)
Plane Geometry is an essential curricular component taught in schools of basic education of the State of Ceará and the other States which it is present in high school reform proposed by the MEC recently. It helps develop a critical view for society, being very applied in practice in our daily life, as duplications of streets, pedestrian strip, cycle paths, as a change in urban mobility, changing the city’s road network and other things, and applied in pratice of different human activities: engineering, agriculture, livestock, commerce, arts. For this reason, this dissertation addresses a concern of the teacher in experimenting with work alternatives that can stimulate the teaching and learning of Plane Geometry by means of new strategies, aiming to promote a relevant and differentiated learning in the teaching of the concepts of rectangles area, adding a contextualisation and meaning of them in order to facilitate student learning. The main focus ofthe work is to arouse students’ interest in geometric knowledge and develop and improve mathematical skills related to day-today situations. The action strategies included the use of measurement tools at various scales and concrete material aiming at the ludic learning, constructing the concepts necessary for the realization of the activities not just in the classroom but also outside the classroom